Delayed laparoscopic cholecystectomy for a patient with coronavirus disease 2019 who developed gangrenous cholecystitis: a case report - Yurie Yoshida; Tomohiro Iguchi; Norifumi Iseda; Kosuke Hirose; Takuya Honboh; Noriko Iwasaki; Seiya Kato; Noriaki Sadanaga; Hiroshi Matsuura (Surgical Case Reports)
Abstract Background Gangrenous cholecystitis has a high risk of perforation and sepsis; therefore, cholecystectomy in the early stage of the disease is recommended. However, during the novel coronavirus disease 2019 (COVID-19) pandemic, the management of emergent surgeries changed to avoid contagion exposure among medical workers and poor postoperative outcomes. Case presentation A 56-year-old man presented to our hospital with abdominal pain. Computed tomography revealed intraluminal membranes, an irregular or absent wall, and an abscess of the gallbladder, indicating acute gangrenous cholecystitis. Early laparoscopic cholecystectomy seemed to be indicated; however, a COVID-19 antigen test was positive despite no obvious pneumonia on chest computed tomography and no symptoms. After discussion among the multidisciplinary team, antibiotic therapy was started and percutaneous transhepatic gallbladder drainage (PTGBD) was planned for the following day because the patient’s vital signs were stable and his abdominal pain was localized. Fortunately, the antibiotic therapy was very effective, and PTGBD was not needed. The cholecystitis improved and the patient was discharged from the hospital on day 10. One month later, laparoscopic delayed cholecystectomy was performed after confirming a negative COVID-19 polymerase chain reaction test result. The postoperative course was uneventful, and the patient was discharged on postoperative day 2 in satisfactory condition. Conclusion We have reported a case of acute gangrenous cholecystitis in a patient with asymptomatic COVID-19 disease. This report can help to determine treatment strategies for patients with gangrenous cholecystitis during future pandemics.